Hypobaric Hypoxia (Altitude of Residence) and Age Determines Hemoglobin Levels in Peruvian Children Between 6 and 35 Months Old - Leon-Abarca, Juan Alonso (2019)
INTRODUCCIÓN: There is a lack of population studies regarding factors that impact hemoglobin levels in children of a country with varying altitudes of residence.